Au nanoflower film-based stretchable biosensors for in situ monitoring of superoxide anion release in cell mechanotransduction. Issue 18 (15th August 2022) - Zhao, Xu; Peng, Meihong; Wang, Jialu; Chen, Shutong; Lin, Yuqing
Abstract : Cell mechanotransduction plays an important role in vascular regulation and disease development. Abstract : Cell mechanotransduction plays an important role in vascular regulation and disease development. Excessive accumulation of ROS, especially superoxide anion radicals (O2 ˙ − ), is closely related to cardiovascular diseases. Lately, NADPH oxidases, which are the major source of O2 ˙ − production in vascular tissues, have been demonstrated to be involved in cardiovascular diseases. Therefore, in situ and real-time monitoring of superoxide anions (O2 ˙ − ) is essential for exploring the mechanisms of mechanotransduction associated with NADPH oxidase function in living cells. Here we report a rationally designed ultrasonication-assisted approach for growing Au nanoflower films on a flexible surface, which serves as the desired interface for cysteine and superoxide dismutase (SOD) anchoring to form a flexible and stretchable electrode (SOD/Cys/Au SE). The SOD/Cys/Au SE shows good stretchability, fast electron-transfer rates, and high selectivity to measure O2 ˙ − released from cells during the stretching states. Our strategy provides a basis for developing more sophisticated stretchable biosensing tools to induce and monitor transient biochemical signals during cell mechanotransduction.